Later-Life Mortality and the Repeal of Federal Prohibition - David S. Jacks; Krishna Pendakur; Hitoshi Shigeoka; Anthony Wray (Institute of Labor Economics (IZA), 2023)
Despite a recent and dramatic re-evaluation of the health consequences of alcohol consumption, very little is known about the effects of in utero exposure to alcohol on long-run outcomes such as later-life mortality. Here, we investigate how state by year variation in alcohol control arising from the repeal of federal prohibition affects mortality for cohorts born in the 1930s. We find that individuals born in wet states experienced higher later-life mortality than individuals born in dry states, translating into a 3.3% increase in mortality rates between 1990 and 2004 for affected cohorts.
Keywords: H73; I18; J18; N32; 330; alcohol; federal prohibition; in utero exposure; later-life mortality